Immune gene expression in kidney biopsies of lupus nephritis patients at diagnosis and at renal flare. Issue 7 (25th May 2018) - Mejia-Vilet, Juan M; Parikh, Samir V; Song, Huijuan; Fadda, Paolo; Shapiro, John P; Ayoub, Isabelle; Yu, Lianbo; Zhang, Jianying; Uribe-Uribe, Norma; Rovin, Brad H
Abstract: Background: Up to 50% of lupus nephritis (LN) patients experience renal flares after their initial episode of LN. These flares contribute to poor renal outcomes. We postulated that intrarenal immune gene expression is different in flares compared with de novo LN, and conducted these studies to test this hypothesis. Methods: Glomerular and tubulointerstitial immune gene expression was evaluated in 14 patients who had a kidney biopsy to diagnose LN and another biopsy at their first LN flare. Ten healthy living kidney donors were included as controls. RNA was extracted from laser microdissected formalin-fixed paraffin-embedded kidney biopsies. Gene expression was analyzed using the Nanostring nCounter ® platform and validated by quantitative real-time polymerase chain reaction. Differentially expressed genes were analyzed by the Ingenuity Pathway Analysis and Panther Gene Ontology tools. Results: Over 110 genes were differentially expressed between LN and healthy control kidney biopsies. Although there was considerable molecular heterogeneity between LN biopsies at diagnosis and flare, for about half the LN patients gene expression from the first LN biopsy clustered with the repeated LN biopsy. However, in all patients, a set of eight interferon alpha-controlled genes had a significantly higher expression in the diagnostic biopsy compared with the flare biopsy. In contrast, nine tumor necrosis factor alpha-controlled genes had higher expression in flare biopsies. Conclusions: There is significant heterogeneity in immune-gene expression of kidney tissue from LN patients. There are limited but important differences in gene expression between LN flares, which may influence treatment decisions.